Seismic Performance of High-Ductile Fiber-Reinforced Concrete Short Columns - Mingke Deng; Yangxi Zhang (Advances in Civil Engineering)
This study mainly aims to investigate the effectiveness of high-ductile fiber-reinforced concrete (HDC) as a means to enhance the seismic performance of short columns. Six HDC short columns and one reinforced concrete (RC) short column were designed and tested under lateral cyclic loading. The influence of the material type (concrete or HDC), axial load, stirrup ratio, and shear span ratio on crack patterns, hysteresis behavior, shear strength, deformation capacity, energy dissipation, and stiffness degradation was presented and discussed, respectively. The test results show that the RC short column failed in brittle shear with poor energy dissipation, while using HDC to replace concrete can effectively improve the seismic behavior of the short columns. Compared with the RC short column, the shear strength of HDC specimens was improved by 12.6–30.2%, and the drift ratio and the energy dissipation increases were 56.9–88.5% and 237.7–336.7%, respectively, at the ultimate displacement. Additionally, the prediction model of the shear strength for RC columns based on GB50010-2010 (Chinese code) can be safely adopted to evaluate the shear strength of HDC short columns.